Polynuclear copper(II) complexes with hexadentate Schiff base directed by the counter ion. Syntheses, crystal structures and magnetic properties - Buta, Ildiko; Cseh, Liliana; Cretu, Carmen; Aparaschivei, Diana; Maxim, Catalin; Loennecke, Peter; Hey-Hawkins, Evamarie; Stanica, Nicolae; Ohler, Eva; Rentschler, Eva; Andruh, Marius; Costisor, Otilia (Inorganica Chimica Acta, 2018)
Four new complexes, [Cu9L6(µ3-ClO4)2](ClO4)4·4CHCl3 1, [Cu3L2(H2O)2](ClO4)2·3H2O 2, [Cu6L4(N3)2](ClO4)2 3 and [Cu2L(CH3COO)2] 4, where H2L stands for the Schiff base N,N′-bis[(2-hydroxybenzilideneamino)-propyl]-piperazine, were obtained and structurally characterized. Compounds 1, 2 and 3 contain the Cu3L22+ entities in which L2− acts in an unsymmetrical mode with N3O donor set wrapped around marginal copper(II) and with the remained NO sets bound to the central copper ion. The marginal copper(II) ions are in distorted square pyramidal environment, whereas that of the central one is square planar. In 1, the peripheral copper(II) ions (Cu1) are disposed linearly with a two-fold axis passing through the central Cu2 and with the Cu1⋯Cu2 and Cu2⋯Cu1′ distances of 6.755 Å. The linear trinuclear units are bridged by a rare µ3-1,2,3 perchlorate ligand thus describing a 2D network. In [Cu3L2(H2O)2](ClO4)2·3H2O, the Cu3L22+ unit is capped by two water molecules. Here, due to the intramolecular hydrogen bonds, the metal ions are disposed in the corner of a triangle with the Cu1⋯Cu2, Cu1⋯Cu3 and Cu2⋯Cu3 distances of 5.976, 5.314 and 5.760 Ǻ, respectively. In [Cu6L4(N3)2](ClO4)2, two Cu3L22+ units are bridged by two azido groups thus forming a macrocycle of six copper(II) ions. In [Cu2L(CH3COO)2], L2− acts as a symmetrical binucleatig ligand through the two N2O sets disposed on each side of the piperazine ring and pointed away in opposite directions. The square pyramidal environment of copper is achieved by chelate acetato co-ligand.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Coordination polymers; Copper(II) complexes; Perchlorate; Schiff base